Adrift (2018) [videorecording (DVD)] - Woodley, Shailene; Claflin, Sam, 1986-; Palmer, Grace; Ashcraft, Tami Oldham, 1960- (Universal Pictures Home Entertainment, 2018)
Based on the true story of survival, a young couple's chance encounter leads them first to love, and then on the adventure of a lifetime as they face one of the most catastrophic hurricanes in recorded history.